Peranan Knowledge Management dalam Pengembangan Laporan Keuangan pada Perkebunan Kelapa Sawit - Muhammad Sapruwan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
Knowledge Management is the process of transformation of individual knowledge stored (Tacit Knowledge) into knowledge that is open (Explicit Knowledge). Knowledge of the process of preparation of financial statements in in each individual employee must be transformed into a knowledge company. Differences in the financial statements of palm oil plantations with the financial statements in general are: a) the existence of plant investment (Nurseries, Land Clearing, Up keep Plants) and the Fixed Assets Generating Plant (TM); and b) on the operational unit, palm oil plantations financial statements only contains information on cost alone, not including the cost of activities that are in the head office, as well as a representative unit. The methodology used is the Knowledge Conversion Model Nonaka & Takeuchi, the narrative-descriptive analysis, which describes the knowledge of preparation of financial. From the results of this study obtained by the process of preparation of financial statements in the palm oil plantation companies.